Antibacterial studies and statistical design set data of quasi zinc oxide nanostructures. Issue 38 (31st March 2016) - Wahab, Rizwan; Khan, Farheen; Mishra, Yogendra Kumar; Musarrat, Javed; Al-Khedhairy, Abdulaziz A.
Abstract : The analytical techniques employed for the ZnO nanostructures, which showed potential effect on bacteria's ( E. coli, S. aureus and K. pneumoniae ) growth. The recorded spectra obtained at 600 nm by UV-vis spectrophotometry. Abstract : The present paper describes a systematic study of bacterial growth measured and analysed via UV-visible spectroscopy, which reveals a strong dependence on pH. The morphology of the zinc oxide (ZnO) nanostructures (from sheets to flowers) varies with respect to change in pH and hence their different abilities to inhibit the bacterial ( E. coli, S. aureus and K. pneumoniae ) densities. The solution of zinc acetate dihydrate (Zn(CH3 COO)2 ·2H2 O) was optimized by the addition of NaOH and HCl to obtain various pH values, ranging from pH 7 to 12. The optimized (pH 7, 10 and 12) solutions of zinc acetate dihydrate were further refluxed to obtain the different morphologies, and subsequently qualitative and quantitative determinations were studied. Absorption spectra of the resulting solutions were recorded at desired pH values, and all measurements were obtained at 600 nm with respect to corresponding control solution or blank. The linearity of the proposed method was evaluated at five concentration levels in the range from 0.5 to 2.0 μg mL −1 . Minute quantities of the different morphological nanostructures were used to determine the analytical parameters, such as correlation coefficient ( r 2 = 0.9995, 0.9998, 0.9990), limit of detection (LOD, 0.053, 0.027 and 0.072 μg mL −1 ), limit of quantitation (LOQ, 0.016, 0.083 and 0.220 μg mL −1 ), respectively. Relative standard deviation and quantitative recoveries (RSD%) range from 0.113 to 1.58% and 98.66–100.88%. The morphologies of bacteria ( E. coli, S. aureus and K. pneumoniae ) and their interactions with synthesized ZnO nanostructures were analysed with Bio-TEM. The study suggests that the grown ZnO nanostructures with variable morphologies exhibit good accuracy and precision, revealed by statistical parameters and recovery data.